The Effect of Strokemash Training Method with Play Training Method on the Smash Ability of Badminton Players of SMPN 4 Koto Baru - Abdul Sattar; Dian Estu Prasetyo; Maldin Ahmad Burhan (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2023)
The purpose of this study was to determine the effect of the stroke smash training method and the playing practice method on the smash ability of badminton players at SMP N 4 Koto Baru. This research is a type of quantitative research using an experimental method approach. While the form of research design used is